Minimally manipulated adipose derived mesenchymal stromal cells and osteoarthritis: A narrative review - Akkawi, Ibrahim; Draghetti, Maurizio; Zmerly, Hassan (Acta Biomedica Atenei Parmensis, 2022)
Human mesenchymal stromal cells (MSCs) have increasingly been used to treat osteoarthritis (OA) related pain and dysfunction, due to their capacity for regeneration and anti-inflammatory effects. Adipose-derived MSCs are characterized by their abundance, ease of access, easy isolation procedures, high lipoaspirate stromal cell production, quicker multiplication of cells, and less pain and morbidity during harvesting. These cells are typically enzymatically derived from adipose tissue but this technique has complicated regulatory problems. To address this problem, a new technique has been created to extract and process adipose tissue without expansion and the use of enzymes to produce autologous minimally manipulated adipose-derived MSCs. Recent studies have confirmed that this treatment is an effective and promising method for treating pain and improving joint function in patients affected by OA with a very low percentage of complications at short to mid-term follow-up.